Microplastic fragments in digestive tracts of fish from the coastal waters of Kuantan - Abdul Rahman, Nur Raihanah; Miskon, Mohd Fuad; Razali, Azaima (Faculty of Applied Sciences, Universiti Teknologi MARA Shah Alam, Selangor, Malaysia., 2021)
A pilot study of microplastics ingestion by the marine biota was carried out in Kuantan area. Fish samples consisting of five species were obtained from the fish markets in Kempadang and Pantai Sepat, Kuantan, Pahang. These fish are typically caught around 5 nautical miles from the coast. The gastrointestinal tracts of the fish were dissected and placed in 80 % of ethanol for preservation. Then, a 10 M of NaOH alkaline solution was used to digest the gastrointestinal tracts before it was filtered to isolate the microplastics. The physical characteristics of microplastics were analyzed under the microscope. Types of polymer of the isolated microplastics were identified using Fourier-transform infrared (FTIR) spectroscopy. The result showed the most found microplastics in the gastrointestinal gut was polyacrylamide. Additionally, the most abundant shape of microplastics found was threadlike. It can be suggested that the presence of threadlike microplastics is due to the fishing activities in the area.